Incidence of BCL-2 gene rearrangements in Argentinean non-Hodgkin lymphoma patients: Increased frequency of breakpoints outside of MBR and MCR - Noriega, Maria Fernanda (2004)
The t(14;18)(q32;q21) is the most frequent cytogenetic abnormality observed in follicular lymphoma (FL), but also occurs in diffuse large B-cell lymphoma (DLBCL). We have evaluated the frequency of this translocation in 106 Argentinean non-Hodgkin lymphoma (NHL) patients: 83 with diagnosis of FL and 23 with DLBCL. Nested (N) and long-distance PCR (LD-PCR) approaches were used. By N-PCR, a total of 42 (51%) FL cases showed BCL-2 rearrangement: 28 (34%) for major breakpoint region (MBR) and 14 (17%) for minor cluster region (mcr). By LD-PCR, additional 23 (28%) new positive cases were found: 10 (12%) for MBR and 13 (16%) for mcr. These data make a total of 65 (78%) positive cases for BCL-2 gene rearrangements. In DLBCL cases, N-PCR detected two (9%) cases with the MBR breakpoint and one (4%) with mcr. Seven (30%) new positive cases by LD-PCR were found: four (17%) for MBR and three (13%) for mcr, showing a total of 10 (43%) positive cases. Thus, both FL and DLBCL had high frequencies of breakpoints located between MBR and mcr clusters. Our N-PCR results in FL (51%; 95% CI, 40-62%) showed statistical differences with respect to the pooled data from USA (P < 0.0001) and overlapped with the frequencies from Asia and Europe. In DLBCL, no significant differences with respect to the literature were found. This data support the idea that FL may be a heterogeneous malignancy with distinct molecular pathogenesis and suggest that the geographic differences may be related with the distribution of breakpoints that are widely spread throughout the sequence stretch between MBR and mcr. © 2003 Elsevier Inc. All rights reserved.